rab-27 acts in an intestinal pathway to inhibit axon regeneration in C. elegans. - Alexander T Lin-Moore (Public Library of Science (PLoS), 2021)
Injured axons must regenerate to restore nervous system function, and regeneration is regulated in part by external factors from non-neuronal tissues. Many of these extrinsic factors act in the immediate cellular environment of the axon to promote or restrict regeneration, but the existence of long-distance signals regulating axon regeneration has not been clear. Here we show that the Rab GTPase rab-27 inhibits regeneration of GABAergic motor neurons in C. elegans through activity in the intestine. Re-expression of RAB-27, but not the closely related RAB-3, in the intestine of rab-27 mutant animals is sufficient to rescue normal regeneration. Several additional components of an intestinal neuropeptide secretion pathway also inhibit axon regeneration, including NPDC1/cab-1, SNAP25/aex-4, KPC3/aex-5, and the neuropeptide NLP-40, and re-expression of these genes in the intestine of mutant animals is sufficient to restore normal regeneration success. Additionally, NPDC1/cab-1 and SNAP25/aex-4 genetically interact with rab-27 in the context of axon regeneration inhibition. Together these data indicate that RAB-27-dependent neuropeptide secretion from the intestine inhibits axon regeneration, and point to distal tissues as potent extrinsic regulators of regeneration.